An Implementation Of Electronic Traffic Law Enforcement Against Traffic Violations - Dodiawan S Dodiawan S; Arpangi Arpangi (Law Development Journal, 2021)
This study aims to identify and analyze the implementation of Electronic Traffic Law Enforcement and the obstacles in implementing ETLE in the context of law enforcement against traffic violations at the Blora Police Traffic Unit. The approach method used is sociological juridical, descriptive analytical research specifications, types and sources of data using primary and secondary data, data collection methods are field studies and literature studies, while the data analysis method uses qualitative analysis. The results showed that ETLE implementation is carried out in several stages, starting from CCTV installation, data recording of violators, identification of Smart Resident Center (SRC), sending letters to violators, confirmation, issuing ticket and BRIVA code, to blocking of STNK. This is a manifestation of law enforcement against traffic violations while still paying attention to the principles of justice, legal certainty and expediency. However, in practice there are several obstacles, namely the immediate addition of CCTV installations with adequate camera quality, notifying the vehicle owner that he has committed a violation and to immediately change the name of the vehicle, conducting raid operations on the highway, as well as conducting socialization and education about traffic rules and regulations ETLE.